Menanamkan Kreativitas Anak Panti Asuhan Atap Langit Yogyakarta Dengan Mengelola Limbah Botol Plastik - Pudma Febby Mandalika, Wayan (Sinesia : Jurnal Pengabdian Masyarakat, 2024)
Plastic bottle waste has always been an important issue in natural pollution, both land and ocean pollution. Creativity is an important educational and life demand today. People who have creative skills are always needed by the environment because they can overcome problems that continue to develop. The aim of the activity is to instill creativity in the children of Atap Langit in managing plastic bottle waste into interesting handicrafts. This community service activity was carried out at the Atap Langit in Yogyakarta. This service examines efforts to instill creativity in processing plastic bottle waste into handicrafts using qualitative descriptive methods. The posttest results showed that the participants already had the character of environmental cleanliness and creativity in managing plastic bottle waste. The final result based on the pretest and posttest results can be categorized as successful and satisfactory, the child is able to do a handicraft according to the instructions. In this way, the activity of managing plastic bottle waste into handicrafts can instill creativity in the children of Atap Langit Orphanage.